China's electric car frustrations. (January 2015) - Wan, Zheng; Sperling, Daniel; Wang, Yunshi
Highlights: China' ambitions to build a large PEV industry and market are not being realized as fast as hoped. Large vehicle incentives and demonstration programs have had limited effect. Protectionism reduces the PEV market and undermines national PEV policy. Shifting technology strategies and conservative behavior of manufacturers are also concerns. Stronger leadership is needed to overcome the challenges. Abstract: By 2020, the vehicle population in China will likely exceed 280 million—exacerbating national energy security, urban air pollution, and traffic congestion. In response, many local and regional governments in China are pursuing an expanding array of measures to restrain growth in personal vehicle ownership and, along with the central government, reducing emissions and energy use of vehicles. One prominent strategy is the promotion of new energy vehicles, especially plug-in electric vehicles (PEVs). Large subsidies were offered—up to 27, 600 (171, 000 RMB) per vehicle in some regions, including almost 9200 (57, 000 RMB) from the central government—which suggests that China is making a major commitment to PEVs. But sales have been meager. In 2013, only 17, 600 PEVs, mostly buses and utility trucks, were sold, less than 0.1% of total civilian vehicle sales. Several factors explain the failure of PEV sales to take off: (1) protectionism by local governments; (2) uncertainty over which electric-drive vehicle technologies to promote and what consumers are willing to pay, (3) lagging investments in charging infrastructure, and (4) conservative investment behavior by automakers and battery manufacturers. The central government issued directives to local governments in late 2013 to reduce barriers to out-of-town companies, resulting in modest sales increases in early 2014, but a more coherent, broader, and effective set of policies, incentives, and strategies are needed to overcome consumer and industry resistance and the lack of charging infrastructure.